(untitled) (Research, Society and Development, 2024)
Introduction: Congenital syphilis is an infectious disease caused by the bacterium Treponema pallidum with gestational transmission, which has a significant impact on the health of the fetus. Although prevention of this disease during pregnancy is safe and the treatment effective, its incidence has remained high in several countries, especially Brazil, which makes congenital syphilis a serious global public health problem that needs to be studied. Objective: To analyze the protocols for the treatment of congenital syphilis in Brazil and the United States in order to identify possible reasons for the increase in the incidence rate of this disease in different countries with different territorial areas, development rates and economies. Method: This is a scoping review based on a search of the PubMed database for the period 2013 to 2023. Results: One of the main factors responsible for the difference in congenital syphilis rates in each country is economic and territorial differences. In addition, the offer of screening for syphilis during pregnancy is not homogeneous throughout the territory of the countries analyzed and there are differences in the form of access for each social group within the same country. Conclusion: The protocols of the two countries analyzed are adequate and the biggest problem is adequate access to information and screening during prenatal care, treatment during pregnancy, for both the pregnant woman and her partner, and after childbirth.